Rosa damascena together with brown sugar mitigate functional constipation in children over 12 months old: A double-blind randomized controlled trial. (15th November 2022) - Imanieh, Mohammad Hadi; Honar, Naser; Mohagheghzadeh, Abdolali; Haghighat, Mahmood; Dehghani, Seyed Mohsen; Mosleh, Ghazaleh; Ataollahi, Maryam; Safarpour, Heidar; Darban, Behnaz; Karbasian, Fereshteh; Safarpour, Ali Reza; Hassani, Amir Hossein; et al.
Abstract: Ethnopharmacological relevance: Rosa × damascena Herrm., known as damask rose, is a bushy shrub that is found abundantly in Fars province, Iran. This species has been used in Iranian traditional practices for the treatment of abdominal pain and constipation, as gastrointestinal diseases. Brown sugar ( Saccharum officinarum L.) has also shown laxative effects in pediatric patients with functional constipation. Aim of study: This study aimed to compare the effects of Polyethylene Glycol (PEG) and a syrup made of R. damascena and brown sugar on the treatment of functional constipation in children aged above 12 months. Materials and methods: This double-blind randomized clinical trial was performed on 100 patients. One group received PEG and the other received an herbal syrup containing the decocted extract of 0.1 g R. damascena petals mixed with 0.85 g brown sugar per 1 mL. The patients were followed up for two and four weeks and their progresses were recorded. Results: The cure rate was 100% in the R. damascena group and 91.7% in the control group. R. damascena and brown sugar syrup had an odds ratio of 1.09 in the treatment of functional constipation compared to PEG, but the difference was not statistically significant. The only adverse effect detected in the R. damascena group after four weeks was the bad taste of the medication that was too sweet. Nonetheless, this could be solved during the pharmaceutical processes. Conclusion: The R. damascena extract and brown sugar syrup can be used as an effective, safe, and inexpensive agent in the treatment of functional constipation. Graphical abstract: Image 1